Outcome after acute osteomyelitis in preterm infants. - Williamson, J B (1990)
Eight cases of skeletal infection in preterm infants were studied. All the infants were systemically unwell, with polymorpholeucocytosis. Diagnosis was by blood culture, and any radiographic changes were apparent at the time of presentation. Infection was often multifocal, with sites around the knee being most commonly affected. Staphylococcus aureus was the pathogen isolated in six of the eight cases; in these treatment with fusidic acid was effective and well tolerated, even at doses that were less than the recommended therapeutic minimum. Even with prompt diagnosis and aggressive treatment orthopaedic sequelae are common.